Comparison of the so-called CGR and NCR cathodes in commercial lithium-ion batteries using in situ neutron powder diffraction. Issue 1 (18th December 2014) - Alam, Moshiul; Hanley, Tracey; Pang, Wei Kong; Peterson, Vanessa K.; Sharma, Neeraj
<x content-type="archive" xml:space="preserve">Abstract</x> The evolution of the 003 reflection of the layered Li(Ni, Co, Mn)O2 (CGR) and Li(Ni, Co, Al)O2 (NCR) cathodes in commercial 18650 lithium-ion batteries during charge/discharge were determined using in situ neutron powder diffraction. The 003 reflection is chosen as it is the stacking axis of the layered structure and shows the largest change during charge/discharge. The comparison between these two cathodes shows that the NCR cathode exhibits an unusual contraction near the charged state and during the potentiostatic step, where the potentiostatic step is recommended by the manufacturer. This feature is not shown to the same degree by the CGR cathode. The behavior is likely related to the compositions of these cathodes, the amount of Li/Ni site mixing and the presence of Al or Mn.